2003
DOI: 10.1002/macp.200350003
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Branching and Crosslinking of Terpyridine‐Modified Copolymers: Complexation and Decomplexation Studies in Diluted Solution

Abstract: A series of poly(methyl methacrylate) copolymers with terpyridine units in the side chains was obtained by free radical polymerization. The free terpyridine units were complexed by iron(II) and zinc(II) ions, and the complexation behavior was studied in detail, utilizing UV‐vis and viscosity titration experiments. Complexation of the polymer chains could be observed, which resulted in characteristic UV‐vis absorption bands and an increase in the solution viscosity. Addition of a strong competitive ligand (hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 37 publications
3
65
0
Order By: Relevance
“…35,50,51 In this study, the reversible complexation/ decomplexation of the membranes with cobalt(II) and iron(II) was observed by the colour switch upon treatment with HEEDTA (Fig. 2C).…”
Section: Characterization and Redox Switch Behaviour Of Apcns Modiedsupporting
confidence: 51%
“…35,50,51 In this study, the reversible complexation/ decomplexation of the membranes with cobalt(II) and iron(II) was observed by the colour switch upon treatment with HEEDTA (Fig. 2C).…”
Section: Characterization and Redox Switch Behaviour Of Apcns Modiedsupporting
confidence: 51%
“…Various investigations of the complexation and decomplexation behavior of MA C H T U N G T R E N N U N G (tpy) 2 architectures have been reported. Either metal-complexing ligands such as hydroxyethylethylenediaminetriacetic acid (HEEDTA) [32] or variations of the pH value [33][34] can be used in most cases to cleave the coordinative bonds in tpy complexes. We found that in the case of Fe (7) 2 2 + , addition of one equivalent of 1,8-diazabicycloA C H T U N G T R E N N U N G [5.4.0]undec-7-ene (DBU) in chloroform is sufficient for complete decomplexation within 12 h at room temperature.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] 2,2Ј:6Ј,2ЈЈ-Terpyridines bearing well-defined π-conjugated substituents at the 4Ј-position are known to exhibit attractive electronic and optical properties. [6,8,10,[14][15][16][17][18][19][20][21][22][23][24][25] When two 2,2Ј:6Ј,2ЈЈ-terpyridine units are introduced at either end of a rigid conjugated spacer, the resulting ditopic bis(terpyridine) ligand enables the synthesis of metallo-supramolecular polymers by coordination with different metal ions. Several publications dealing with the synthesis and characterization of such conjugated terpyrid-ine derivatives were fully characterized by 1 H and 13 C NMR spectroscopy, UV/Vis absorption and emission measurements as well as MALDI-TOF MS.…”
Section: Introductionmentioning
confidence: 99%